Explicit mechanistic insights of Prosopis juliflora extract in streptozotocin-induced diabetic rats at the molecular level - Yousra Nomier; Gihan F. Asaad; Abeer Salama; Marwa E. Shabana; Saeed Alshahrani; Mohammad Firoz Alam; Tarique Anwer; Shahnaz Sultana; Zia ur Rehman; Asaad Khalid (Elsevier, 2023)
Background: The Ancient system of medicine showed the limelight on the use of herbal remedies and was found to possess minimal side effects and acceptable therapeutic outcomes. In this context, Prosopis juliflora gained importance in managing chronic diseases such as cancer, dermatological diseases, and chronic inflammatory disorders. Hence, P. juliflora was selected for further investigation associated with diabetes and inflammation. Aim: The present study aimed to evaluate the anti-diabetic activity in chemically induced experimental rats and explore the nature of phytocomponents that may produce this activity. Methods: Experimentally, diabetes was induced by a single administration of streptozotocin at 50 mg/kg intraperitoneally in Wistar rats. The animals were treated orally with P. juliflora at low and high doses (200 and 400 mg/kg) for 10 days. Blood collected from the retro-orbital plexus was analyzed for parameters like blood glucose levels, insulin, adiponectin, Keap1 and Nrf2. PPAR-γ, AMPK and GLUT 2 levels were analyzed in the pancreatic tissue. Besides, at the end of the experiment, animals were sacrificed, and the pancreatic tissue sections were subjected for histopathological, morphometrical and immune histochemical exploration. The phytochemical composition of the plant was investigated by GC-MS. Results: The administration of P. juliflora higher dose showed a significant decrease (**p< 0.001) in blood glucose levels with a rise in adiponectin, PPARγ, Keap1, Nrf2, Glut 2, and AMPK significantly (**p< 0.001). The inflammatory cytokine TNFα was also estimated and was found to be lowered significantly (**p< 0.001) in test drug-treated animals. Furthermore, in the pancreatic tissue, the number of Islets, the area, and the number of β-cells were improved significantly with the sub-chronic treatment of P. juliflora extract. The structure and function of β-cells were also revamped. Conclusion: The study results demonstrated a significant effect of P. juliflora on glycemic status, inflammatory condition, and the architecture of pancreatic tissue. In the identification and isolation process by GC MS, it was noticed that P. juliflora contained few phytochemical constituents from which it might be considered a promising drug for type 2 diabetes mellitus.